2018
DOI: 10.3389/fimmu.2018.00591
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Natural Killer Cell Response to Seasonal Influenza Vaccination Are Not Influenced by a Synbiotic: a Randomised Controlled Trial

Abstract: Natural killer (NK) cells are an important component of the immune response to influenza infection, but are subject to alteration during aging, which may play a role in impaired response to infection and vaccination in older people. Enhancement of NK cell activity could, therefore, present a means to improve the immune response to vaccination in older subjects, and pre- and probiotics offer an opportunity to modulate antiviral defenses via alteration of the gut microbiota. This study investigated the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 58 publications
6
22
0
Order By: Relevance
“…In addition, neither time (p=0.97) nor treatment group (mean vaccine: 6.50% (95% CI: 5.34%, 7.91%); mean placebo: 5.51% (95% CI: 4.51%, 6.74%), p=0.24) were independently associated with CD56 dim cell counts. For CD56 bright cell counts, time modified the effect of placebo and vaccine groups (p=0.01); wherein CD56 bright count increased by a factor of 1.25 (95% CI: 1.07, 1.46, p=0.01) in the vaccine group but the change in the placebo group was not statistically significant (Table 2), which is consistent with other vaccine studies (Berthoud et al, 2009;Scott-Algara et al, 2010;Przemska-Kosicka et al, 2018).…”
Section: Minimal Variation In Total Nk-cell Frequencies Over Timesupporting
confidence: 86%
“…In addition, neither time (p=0.97) nor treatment group (mean vaccine: 6.50% (95% CI: 5.34%, 7.91%); mean placebo: 5.51% (95% CI: 4.51%, 6.74%), p=0.24) were independently associated with CD56 dim cell counts. For CD56 bright cell counts, time modified the effect of placebo and vaccine groups (p=0.01); wherein CD56 bright count increased by a factor of 1.25 (95% CI: 1.07, 1.46, p=0.01) in the vaccine group but the change in the placebo group was not statistically significant (Table 2), which is consistent with other vaccine studies (Berthoud et al, 2009;Scott-Algara et al, 2010;Przemska-Kosicka et al, 2018).…”
Section: Minimal Variation In Total Nk-cell Frequencies Over Timesupporting
confidence: 86%
“…In contrast, in another study, B. longum bv. Infantis CCUG 52486, combined with a prebiotic GOS, failed to reduce age-related changes in the NK cell response to seasonal influenza vaccination in elderly compared to young individuals [154]. There were only insignificant effects on B-and T-cell profiles in older subjects compared to those of younger counterparts [155].…”
Section: Synbioticsmentioning
confidence: 89%
“…With the clear immune modulatory effects observed, we hypothesized that B. bronchiseptica carriage had the potential to also affect responses to unrelated immunological stimuli, such as vaccination and infection. Of note, possible influences of microbial carriage on vaccination efficiencies are currently being discussed [ 44 , 45 , 46 , 47 , 60 ]. However, we found that B. bronchiseptica carriers mounted a full humoral response to subcutaneous vaccination with a model antigen.…”
Section: Discussionmentioning
confidence: 99%